Role Of Phonetics In Forming The Communicative Competence Of Foreign Russianist Students - Nikolaevna Shutova, Marina; Sergeevich Khromov, Sergey; Vyacheslavovna Nesterova, Tatyana; Gabdulkhakovna Fathutdinova, Venera (Opción, 2019)
The article is concerned with the issues of teaching foreign Russianist stu- dents the Russian phonetics with due regard to their language proficiency (from elementary to advanced levels). Foreign students learning the Russian language complete different tasks in the field of pronunciation, rhythmic patterns and intonation. However, courses on the Russian phonetics mainly aim at teaching students to communicate in a foreign language, i.e. to form their communicative competence.